Penguatan Pengetahuan dan Perilaku Hidup Bersih dan Sehat melalui Kegiatan Promosi Kesehatan dan Pemberantasan Sarang Nyamuk - Utimkesan, Januarius (Yayasan Inspirasi El Burhani, 2026)
Introduction: Environmental-based diseases such as Dengue Hemorrhagic Fever (DHF) remain a major health concern in several remote regions of Indonesia, including the working area of Puskesmas Iwur. Low health literacy, inadequate hygiene practices, and lack of routine vector control contribute to the persistence of mosquito breeding sites and increase the risk of disease transmission. Promoting Perilaku Hidup Bersih dan Sehat (PHBS) or Clean and Healthy Living Behavior and implementing Pemberantasan Sarang Nyamuk (PSN) are essential strategies to reduce this risk and improve community health. Objective: This community service aimed to improve community knowledge and behaviors related to PHBS and PSN as preventive actions against environmental-based diseases, especially DHF. Method: The program was carried out by the Master of Public Health team from Universitas Strada Indonesia in collaboration with Puskesmas Iwur. Activities included coordination, field observation, health education sessions, interactive discussions, and direct demonstration of PSN 3M Plus (draining, covering, and recycling). A pre-test and post-test were administered to measure changes in community knowledge, and data were analyzed descriptively. Result: A total of 43 participants were involved. The average knowledge score increased from 57.12 before the intervention to 71.21 after the intervention, indicating a significant improvement in understanding PHBS and PSN principles. Participants also demonstrated initial positive behavioral changes, including covering water containers and routinely cleaning potential mosquito breeding sites. Conclusion: Health promotion through education and PSN demonstration is effective in improving PHBS-related knowledge and encouraging preventive behavior among communities in remote areas. Continued community engagement and multi-sectoral collaboration are recommended to ensure program sustainability and long-term impact.